Effectiveness of Deep Breathing Relaxation on Anxiety Due to Hospitalization in Preschool Age Children - Nur Ilah Padhila; Iin Inayah; Fauziah Rudhiati (Indonesian Journal of Global Health Research, 2025)
Hospitalization in preschool children causes them to lose control over their environment, resulting in psychological and physical distress, characterized by panic, phobia, obsessive, compulsive, and generalized anxiety disorders. Objective: This study aims to analyze the effectiveness of Deep Breathing Relaxation. on hospitalization anxiety. Method: This study is a quantitative study with a quasi-experimental design of two groups pre and posttest. The sample of this study was preschool children who underwent hospitalization as many as 32 children. This study used the Preschool Anxiety Scale (PAS) instrument which is of international standard with proven validity (r=0.68) and reliability (0.87). The bivariate data analysis used the Wilcoxon test for the intervention group, the Paired T Test for the control group, and Man Whitney test for comparison of intervention group with control, and N-Gain test to see the effectiveness of the intervention. Result: The results of the study showed that hospitalization anxiety in children before Deep Breathing Relaxation averaged 65.75 with the lowest score of 32 and the highest 79 (SD: 13.394). After the intervention, the children's anxiety score decreased, namely an average score of 53.69, the lowest score of 27 and the highest 66 (SD: 12.877). There was a significant difference between the intervention group and the control group with a p value of 0.038 (<0.05), but the N-Gain results showed that the intervention was in the ineffective category (N-Gain: 20.46%).